Study on setting time and compressive strength performance of ordinary portland cement (OPC) paste containing sodium chloride - Rahimah, Embong (2014)
The presence of impurities in concrete system can possess a damaging effect to the structural integrity of concrete material. Alkali silica reaction, scaling, and corrosion are among the deleterious effect caused by the ingression of internal or external substance to the concrete system. Sodium chloride or salt is one of the external agents involved in the process; hence its excessive amount in concrete system is strictly prohibited. Nevertheless, concrete containing salt water is generally known for the higher early-strength, yet lower ultimate strength than plain concrete. Meanwhile, study on the detail mechanism in early age properties are scarcely available, particularly at low salt concentration. Therefore this research was conducted to provide better understanding in the effect of salt water to the hardening mechanism of Portland cement paste and to obtain the optimum salt inclusion that contributes to the enhancement of concrete properties. Analysis on the performance of this reagent was conducted via setting time, compressive strength, and porosity test. Based on the setting time analysis, the inclusion of sodium chloride can extend the initial setting time of cement paste longer than control specimen. Obstruction on the formation of calcium silicate hydrate gel by sodium and chloride ion was one of the possible causes to this phenomenon. Acceleration on the compressive strength development by sodium chloride was also detected. It appears that sodium chloride was able to de-flocculate the coagulated cement particles and reduced the viscosities of cement slurries; hence resulted in faster early hydration process. Based on the results of this research, it can be concluded that sodium chloride inclusion is beneficial to the workability and compressive strength performance of cement paste binder at certain concentration. Improvement of compressive strength was achieved via faster dissolution and hydration of cement particle due to dispersant characteristic presented by sodium chloride.